حضور الدال وغياب المدلول في خطاب محمد الماغوط الشعري - جمشير، يادكار لطيف; حسين، صالح إبراهيم Hussein, Saleh Ibrahim (جامعة صلاح الدين, 2015)
تنهض الدراسة على خطه تتمثل في تمهيد وثلاثة مباحث. ألقى الباحث الضوء في التمهيد على أصول مفهوم الحضور والغياب في المجال الفكري والفلسفي، وفي مجال الدراسات النقدية، كما بين فيه مفهوم الدال والمدلول والعلاقة الجامعة بينهما. حمل المبحث الأول عنوان (حضور ضمير المتكلم وغياب المدلول المشار إليه)، إذ اعتنى الباحث فيه بعلاقة ضمير المتكلم بالمرجع الخارجي، أما المبحث الثاني فعنوانه (حضور ضمير المخاطب وغياب المدلول المشار إليه) فدرس فيه الباحث علاقة ضمير المخاطب بالإحالة المرجعية الخارجية، وأما المبحث الثالث فعنوانه (حضور طرفي الاتصال في (فعل الأمر وصيغه) وغياب المدلول الحقيقي لهما) ليبين دلالة فعل الأمر في الخطاب الشعري الذي يتجاوز مدلوله الحقيقي ليصبح وسيلة نصية لجنب المتلقي إلى المشاركة والتفاعل مع النص.
Muhammad Maghout is one of the most prominent poets of modern Arabic poetry. He was able to leave his mark on the map of modern and contemporary poetry that is through his distinctive poetic style and his profound poetic experience. That poet expresses his life experience with an enjoyable poetic style and deep language in simple template, which makes reader to respond it and interact with it. He is an origin sound of poetic who has devoted a large space of his poetry to express pains of humans in Middle East. In his poetic texts, he shows the image of insult human dignity and the powerful of oppression and tyranny on the neck of Arab people and communities. In his poems, he has a great interest in poetic themes of alienation, awareness and identity. This research has built on a research approach that consists of a preface and three parts. The preface sheds light on the origins of the concept of presence and absence in the field of intellectual and philosophical, in the critical studies. It also sheds light on the concept of discourse intensely. The first chapter is under the title of (The presence of signifier and the absence of signified). It consists of theory summary and three sections. The theory summary sheds light on the subject of relationship of the signifier and the signified and the development of research in this matter, from the swiss famous linguistic (De Saussure) and passing (Charls Sanders Pierce), American philosopher and the dawn to the critic (Roland Bart) and philosopher (Jack Derrida). The first section is under the title (The presence of the
Keywords: الشعراء السوريون -- الماغوط، محمد -- الشعر العربي -- نقد الشعر